Proinflammatory mucosal-associated invariant CD8+ T cells react to gut flora yeasts and infiltrate multiple sclerosis brain - Gargano, Francesca; Guerrera, Gisella; Piras, Eleonora; Serafini, Barbara; Di Paola, Monica; Rizzetto, Lisa; Buscarinu, Maria Chiara; Annibali, Viviana; Vuotto, Claudia; De Bardi, Marco; D’Orso, Silvia; Ruggieri, Serena; et al. (Frontiers in Immunology, 2022)
The composition of the intestinal microbiota plays a critical role in shaping the immune system. Modern lifestyle, the inappropriate use of antibiotics and the exposure to pollution have significantly affected the composition of commensal microorganisms. It is now suggested that the microbiota may have a role in immune-mediated central nervous system (CNS) diseases such as multiple sclerosis (MS), and the ability of intestinal microbiota to sustain an inappropriate immune reaction, such as in autoimmunity, at distant sites has been recently shown in animal models of disease. We found that a distinct population of cells with antibacterial and antifungal activity is expanded in individuals with MS. These cells, named MAIT (mucosal-associated invariant T cells) lymphocytes, preferentially home to the intestine. We collected faecal samples from 27 persons with MS (pwMS) and 18 healthy donors (HD) and we studied the composition of the cultivable gut mycobiota. In these cohorts, 5 pairs of homozygous twins, discordant for MS disease, were included. We found a tendency towards higher fungal abundance and richness in the MS group. Analyzing MS-twin and HS-twin individuals, we observed that MS twins showed a much higher rate of food-associated strains, such as Saccharomyces cerevisiae. We then studied the response of MAIT cells to Saccharomyces cerevisiae and Candida albicans strains isolated from faecal samples to check for possible different response between pwMS and HD. Multiparametric flow cytometry was used to study MAIT cells’ responses (activation, proliferation and cytokine production). We found that MAIT cells from pwMS were significantly more activated and with higher proliferative rates than those from HD. Moreover, we found that MAIT cell activation and proliferation were mediated by IL-23 produced by innate immune cells in response to fungi. Finally, immunofluorescent staining of post mortem brain tissues from persons with multiple sclerosis showed that MAIT cells cross the blood-brain barrier (BBB) and produce pro-inflammatory cytokines in the brain. These results were in agreement with the hypothesis that dysbiosis of the gut microbiota might determine the inappropriate response of a subset of pathogenic mucosal T cells and favour the development of systemic inflammatory and autoimmune diseases.